Utilizing the diamond fraud theory perspective to analyze financial statement fraud - Yasa, Ida Bagus Anom; Thalib, Moch. Mirza Yahya; Wahyuni , Luh Mei (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study aims to test the influence of elements of the fraud diamond theory, including pressure, opportunity, rationalization, and capability, on financial statement fraud. The population in this study were companies in the banking sub-sector listed on the Indonesia Stock Exchange for the period 2020-2022. The sample was selected using a purposive sampling method with four criteria, which resulted in 40 companies with 3 years of observation, so 120 samples were obtained that were worthy of observation. This study uses multiple regression analysis using the SPSS program. In this study, the pressure variable is measured using ROA, opportunity using ineffective monitoring, and rationalization using the total accrual ratio. In contrast, the capability variable is measured using the change of directors. The dependent variable is financial statement fraud measured using earnings management. The study's results indicate that pressure and rationalization have a positive and significant influence on financial reporting fraud in banking sub-sector companies listed on the IDX. On the other hand, opportunities and capabilities do not show a significant influence on financial reporting fraud in these companies.